(untitled) (Bangladesh Veterinarian, 2011)
Twenty four castrated native sheep were grouped (six/group) into four: T1 >3 to ≤ 6; T2 > 6 to ≤ 9; T3 >9 to ≤12 and T4 >12 to ≤ 15 months. Through out the 63 days of experimental period, animals were offered ad libitum urea (3%), molasses (15%) and straw (82%) as a basal diet with concentrate mixture [14% crude protein (CP) & 11.5 MJ metabolizing energy (ME) per kg Dry Matter (DM)] @ 1% of live weight. Five days metabolic trial was conducted towards the end of the feeding trial. Besides, fortnightly live weight change, daily nutrient intake, carcass yield and carcass characteristics were studied. Daily weight gain decreased (P<0.05) with the increasing in age and the growth rate were 79, 63, 55 and 44g/day for T1, T2, T3 and T4, respectively. Higher growth rate in T1 was due to animal’s inherent self-accelerated phase of growth. Feed conversion ratio (FCR; kg feed/kg live weight gain) was significantly (P<0.001) better in T1 (9.2) followed by T2 (13.8), T3 (17.7) and T4 (21.7). Cost per kg of carcass production was lower in T1 (Taka: 239), but the production cost increased in T2 (Taka: 357), T3 (Taka: 440) and T4 (Taka: 515). DM intake (g/kg W0.75) decreased with the increase in age and weight. For each gram increased in live weight gain, it required 7.7 kJ ME and animals achieved zero live weight gain (maintenance energy level) at 377 kJ/kg W0.75/d ME intake. Slaughtered weight, warmed carcass weight and dressing yield (%) of native sheep increased with advancement of age. Dressing yields were 48.5, 49, 51.4 and 55.5% for T1, T2, T3 and T4, respectively. Fat percent increased with increasing age and body fat as percent of live weight were 5.6, 7.7 15.5 and 20.6, respectively for the T1, T2, T3 and T4. As a part of total carcass, the proportional yield of tender loin and hind leg chump, most valued retail cut, decreased with the increased animal age. In the present trial, body weight gain at early stage (6-8 months of age) of life was more economical than at the later stage of life. It is suggests that the optimum market/slaughter age for native sheep maintained under these feeding and management would be at around eight months of age. DOI: 10.3329/bvet.v27i2.7556 Bangl. vet. 2010. Vol. 27, No. 2, 62-73